The Influence of Service Quality and Price Perception on the Intention to Reuse Trans Palu Bus Services - Riyanto, Wahyu; Sutomo, Maskuri; Santi, Ira Nuriya; Farid, Farid (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the effect of service quality and price perception on the intention to reuse the Trans Palu Bus service. Using a quantitative approach, data were collected via online questionnaires from 90 purposively selected respondents. The analysis employed multiple regression through SPSS version 31. Results indicate that service quality and price perception significantly influence repurchase intention both partially and simultaneously. The coefficient of determination shows that these variables explain 46.1% of the variance in repurchase intention, implying the need for service enhancement and pricing strategies to improve customer retention